Wnioskowy tryb ścigania w świetle nowelizacji Kodeksu postępowania karnego z dnia 7 lipca 2022 roku - Justyna Karaźniewicz (Acta Iuris Stetinensis)
The purpose of the article is to analyze and then evaluate the changes made within the procedural aspects of the motion mode of prosecution, which were introduced by the Act of July 7, 2022 on amendments to the Act – Criminal Code and some other acts. They consisted in amending the content of Article 12 of the Criminal Code of Procedure by adding § 4. According to this provision, it will be possible to conduct proceedings ex officio despite the absence of a motion for prosecution of the offence of criminal threats in the two situations: if there is a high probability that the failure to file a motion for prosecution is due to the victim’s fear of reprisals or if the public interest is in favor of it. The analysis used a dogmatic method through exegesis of the legal text, as well as an examination of the literature. The materials of the legislative work were also taken into account, in particular the justification of the draft law, as well as the results of public consultations and opinions submitted before the draft was sent for parliamentary work. The considerations presented in the article allowed a critical assessment of the introduced solution, both from the perspective of the correctness of the legislative process and the essential elements of the new solution. It was pointed out, among other things, the lack of justification of the proposed changes, doubts about the scope of application of the new provision, ambiguities in the interpretation of the premises and the lack of regulation of the essential elements of the new institution. Consequently, a postulate was put forward to remove the introduced Article 12 § 4 of the Code of Criminal Procedure.